Intestinal Acid Sphingomyelinase Protects From Severe Pathogen-Driven Colitis - Meiners, Jana; Palmieri, Vittoria; Klopfleisch, Robert; Ebel, Jana-Fabienne; Japtok, Lukasz; Schumacher, Fabian; Yusuf, Ayan Mohamud; Becker, Katrin A.; Zöller, Julia; Hose, Matthias; Kleuser, Burkhard; Hermann, Dirk M.; et al. (Frontiers in Immunology, 2019)
Inflammatory diseases of the gastrointestinal tract are emerging as a global problem with increased evidence and prevalence in numerous countries. A dysregulated sphingolipid metabolism occurs in patients with ulcerative colitis and is discussed to contribute to its pathogenesis. In the present study, we determined the impact of acid sphingomyelinase (Asm), which catalyzes the hydrolysis of sphingomyelin to ceramide in the course of Citrobacter (C.) rodentium-driven colitis. C. rodentium is an enteric pathogen and induces colonic inflammation very similar to the pathology in patients with ulcerative colitis. We found that mice with Asm deficiency or Asm inhibition are strongly susceptible to C. rodentium infection. These mice harbored increased levels of C. rodentium in the feces and were prone to bacterial dissemination to the systemic organs. In addition, mice lacking Asm activity showed an uncontrolled inflammatory Th1 and Th17 response, which was accompanied by a stronger colonic pathology compared to infected wild type mice. These findings identified Asm as a critical regulator of mucosal immunity to the enteric pathogen C. rodentium.